2022
DOI: 10.1101/2022.08.09.503218
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Labeled lines for fat and sugar reward combine to promote overeating

Abstract: Food is a powerful natural reinforcer that guides feeding decisions. The vagus nerve conveys internal sensory information from the gut to the brain about nutritional value; however, the cellular and molecular basis of macronutrient-specific reward circuits are poorly understood. Here, we monitor in vivo calcium dynamics to provide direct evidence of independent vagal sensing pathways for detection of dietary fats and sugars. Using activity-dependent genetic capture of nutrient-specific vagal neurons activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…In accordance, we found that SucrW 12Wk feeding increased AgRP neuronal activity and caloric intake without significantly altering bodyweight or body composition. These changes in neuronal firing mirror HFDinduced changes to AgRP neuronal firing rate in DIO mice [24,31], though to a lesser extent, likely driven by functional differences in fat-and sugar-sensitive afferents to the hypothalamus and AgRP neurons [33][34][35]77] or even disparate circuitries for hedonic and nutritional sugar preference [40]. Interestingly, fasting failed to further increase the F AP of AgRP neurons suggesting that (1) AgRP neurons are refractory to additional relevant stimuli, or (2) this rate represents a ceiling beyond which AgRP neurons are not able to sustain action potential firing.…”
Section: Discussionmentioning
confidence: 85%
“…In accordance, we found that SucrW 12Wk feeding increased AgRP neuronal activity and caloric intake without significantly altering bodyweight or body composition. These changes in neuronal firing mirror HFDinduced changes to AgRP neuronal firing rate in DIO mice [24,31], though to a lesser extent, likely driven by functional differences in fat-and sugar-sensitive afferents to the hypothalamus and AgRP neurons [33][34][35]77] or even disparate circuitries for hedonic and nutritional sugar preference [40]. Interestingly, fasting failed to further increase the F AP of AgRP neurons suggesting that (1) AgRP neurons are refractory to additional relevant stimuli, or (2) this rate represents a ceiling beyond which AgRP neurons are not able to sustain action potential firing.…”
Section: Discussionmentioning
confidence: 85%
“…Dietary preferences are largely learned 69 and this process involves reward-based associations. 46, 52, 69, 70 In light of the increased preference for nutrients caused by dHPC neurons (Fig 2), we hypothesize that these neurons are involved in reinforcement learning. To address this, we assessed the role of nutrient-responsive dHPC neurons in a flavor-nutrient conditioning task, in which animals are trained to prefer a novel non-nutritive flavor that has been experimentally paired to an intragastric infusion of nutrient (Fig 4A).…”
Section: Resultsmentioning
confidence: 95%
“…46 Thus, we inquired whether separate populations of dHPC neurons are recruited in response to fat and sugar. We used a Fos TRAP mouse 51 with a previously validated approach 46 to compare neuronal activity in response to two separate nutrient infusions in the same mouse (Fig 1K). These mice express an inducible Cre recombinase, iCreER T2 , under the control of an activity-dependent Fos promoter ( Fos TRAP mice), enabling permanent genetic access to neuronal populations based on their activation to a specific, time-restricted stimulus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations